Hearing Loss in Patients of Cleft LIP and Palate - I. J. Gupta; R. N. Sharma; S. K. Bhatnagar; N. Bhatia; N. Somasundran (Indian Journal of Plastic Surgery)
This study showing 65 percent hearing loss in cases of cleft lip and/or palate cases.